The Impact Of The Used Clothing Trade From Singapore On The Economy And Law In Indonesia - Krismansyah, Krismanyah; Firmanto, Aditia Arief; MUslih, Muslih; PBL, Ashiva Jingga; Aziza, Azmirda Fatma; Azoya, Azoya (Universitas Malayati, 2024)
Export and Import is one of international relations in the field of trade. Various export and import commodities have been regulated in clear regulations. However, there are still commodities that have actually been banned from being imported but are still being carried out. One of the Minister of Trade of the Republic of Indonesia Number 51/M-DAG/PER/7/2015 concerning Prohibition of importing Used Clothing. The domino effect is that the more people buy used clothes, the local fashion industry will be shaken. As one of the Government Agencies participating in the effort to eradicate the smuggling of used clothing and the public should not be easily placed by the import price of used clothing which is cheaper than local clothing, because the level of health is not necessarily guaranteed.Keywords : Impact, Import, Use clothes